Molecular mapping of Asian soybean rust resistance in soybean landraces PI 594767A, PI 587905 and PI 416764 - Hossain, Motaher M.; Akamatsu, Hajime; Morishita, Masami; Mori, T.; Yamaoka, Yuichi; Suenaga, Kazuhiro; Soares, Rafael Moreira; Bogado, Alicia Noelia; Ivancovich, Antonio Juan; Yamanaka, Naoki (Wiley, 2019)
Asian soybean rust (ASR), caused by Phakopsora pachyrhizi, is one of the most serious diseases of soybean. The soybean landraces PI 594767A, PI 587905 and PI 416764 previously showed high levels of resistance to a wide range of ASR fungus, while the genetic basis of the resistance has yet to be understood. In this study, the ASR resistance loci were mapped using three independent mapping populations, POP‐1, POP‐2 and POP‐3 derived from crosses BRS184 × PI 594767A, BRS184 × PI 587905 and BRS184 × PI 416764, respectively. In each population, the resistance to ASR segregated as a single gene, but the resistance was dominant in PI 594767A and PI 587905 and incompletely dominant in PI 416764. The resistance genes from both PI 594767A and PI 587905 were mapped on chromosome 18 corresponding to the same location as known resistance locus Rpp1. Quantitative trait locus (QTL) analysis performed on POP‐3 identified the putative ASR resistance locus in PI 416764 on the defined region of chromosome 6 where Rpp3 was located. The QTLs detected by the mapping explained about 67–72% of the phenotypic variation in POP‐3. Cluster analysis based on disease reactions to 64 ASR populations demonstrated the presence of at least two types of functional resistant Rpp1 alleles: strong and weak allele(s), e.g. soybean accession PI 594767A and PI 587905 carry the strong resistant Rpp1 allele(s). Introducing or pyramiding strong Rpp1 allele(s) in elite soybean cultivars is expected to be useful against the South American rust population.